The Impact of Tenth Grade Students’ Grammar Mastery and Anxiety on Their English Achievement - Febriyanti, Nani; Sari, Artanti Puspita; Firdaus, Masagus (Yayasan Sembilan Pemuda Indonesia, 2023)
The aim in the study is to comprehend and determine how students’ anxiety and ability to use grammar influence their English achievement in the X-grade at three schools in the districts of Semendawai Barat and Cempaka, OKU East regency. For this study, ex post facto design was applied. At SMA N 1 Cempaka, SMA N 2 Semendawai West, and SMA N 1 Semendawai West, this research was carried out. The 96 participants from 3 different schools made up the sample. In this study, several data testing methods were employed, including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests, autocorrelation tests, correlation studies of the r-product moment, simple regression analyses, and double regression analyses. The findings of this study demonstrated that: 1) grammar proficiency significantly influences English success; 2) The achievement of students in English has been considerably impacted by students’ worry; and 3) Although only by 10.8%, grammatical proficiency and anxiety together have a considerable impact on English learning outcomes.